Effect of zinc on milkfish nastar-cookies to albumin and hemoglobin levels in HIV/AIDS patients - Hindaryani, Nurul; Sofro, Muchlis Achsan Udji; Agustini, Tri Winarni (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2020)
Background: Human Immunodeficiency Virus (HIV) destroys the antibody system, which causes faster protein breakdown resulting in lower albumin concentration. Zinc supplementation when added to protein in milkfish flour may increase albumin and zinc levels that associated with activity of the aminolevulinic acid dehydrase (ALAD) that synthesizes heme. Objectives: This study aimed to prove the effect of zinc and milkfish flour addition on albumin and hemoglobin levels in HIV/AIDS patients.Methods: An experimental study with randomized pre and post-test with the control group design using control subjects (n=17) and treatment (n=21). The administration of milkfish nastar with zinc to treatment group was 100 g/day for 60 days, while the control group was given milkfish nastar without zinc 100 g/day for 60 days. The measurement of albumin level used auto photometric with enzymatic color test methods and reticulated method for hemoglobin level measurement conducted before and after treatments. Data were analyzed using Shapiro-Wilk, paired t-test, and independent t-test with a significance value at p<0.05. Results: The means of albumin level in the treatment group increased by 7.03%, while the control group increased by 4.33% (p>0.05). Means of hemoglobin level in the treatment group increased by 12.0%, while the control group increased by 7.9% (p<0.05). Conclusion: Albumin and hemoglobin levels increased after milkfish nastar administration with zinc addition in HIV/AIDS patients.